The Sources of the Historia Augusta Re-examined - Rohrbacher, David (Histos, 2013)
The first step toward unraveling the mysteries of the late Roman biographical collection called the Historia Augusta is to separate out the authentic historical material from the fictions which the author offers in abundance. This article presents a careful re-examination of the evidence for the sources of each section of the work, concluding that the author draws upon Enmann’s Kaisergeschichte and its progeny, Marius Maximus, Herodian, Dexippus, and, for the last Lives, a Greek source, perhaps Eunapius.